Virtual Education Environment For Engineering Courses - Munkhtuya, Davaatsagaan (2003)
This research studies a virtual education environment for engineering courses. The virtual education environment consists of networked functional blocks where each functional block is a combination of hardware and software that provides a specific function. Specific service environments such as a virtual learning environment and virtual teaching environment can be derived by integrating different sets of functional blocks. The research involves the development of all the different functional blocks to demonstrate the viability of Virtual Education Environment, with specific focus on the knowledge base and interface for the learning environment. The development of the knowledge base, the multimedia database, and user interface would provide hands-on experience in integrating new technologies.